Poézia - Sládkovič, Andrej, 1820-1872; Kraus, Cyril, 1928-2012 (Bratislava Tatran, 1976)
Marína
Detvan
Milica
Svätomartiniáda
Gróf Mikuláš Šubič Zrínsky na Sihoti
Keywords: slovenská poézia; Slovak poetry